Judicial jurisdiction of the State Council in light of the provisions of the 2020 Constitution - Benaichouche, Omar; Eldjilali, Ben Tayeb (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2024)
In the 2020 constitutional amendments in Algeria, the founders of the constitution approved the creation of an administrative appellate court, and thus the contract of the administrative judicial structure (administrative courts, administrative appellate courts, Council of State) was completed, as the legislator needed to redistribute judicial jurisdiction among the three judicial bodies, to ease the pressure on the Council of State, and devote itself to exercising its advisory and judicial powers, which prompted us to ask about the judicial jurisdiction of the Council of State in light of the latest legal amendments. To address these issues, we decided to divide the plan into two axes: On the first axis, we addressed the organization of the judicial bodies of the Council of State, while on the second axis, we addressed the judicial jurisdiction of the Council of State. This research uses a descriptive analytical approach, as well as an inductive approach, by extrapolating legal texts related to the judicial functions of the Council of State. The 2020 constitutional amendments and the accompanying legal amendments that will strengthen the principle of two-tier litigation in administrative matters, are considered one of the most important basic principles of the judiciary, and enshrine legal protection and supervision of the work of public institutions and administrative administration, and embody the principle of legitimacy. The establishment of administrative courts of appeal has significantly contributed to the harmonious redistribution of judicial jurisdiction among Algeria's administrative judicial structures. The research recommends the importance for the legislative authorities to amend the internal regulations of the Council of State, to adapt to recent legal amendments, including the 2020 constitutional amendments, Organic Law No. 22-11 amending and supplementing Law 98-01, and Law 22-13 amending and supplementing Law 08-09, including the Codes of Civil and Administrative Procedure.